Technical-tactical combat behavior in the wrestling finals of the Olympic Games 2016 in comparison to London 2012 - Tünnemann, H. (International scientific and professional conference on wrestling: "Applicable research in wrestling", 2017)
Due to television broadcasts the world takes a picture of the attractiveness not only of our sport, but also of all Olympic sports. Therefore it is interesting to analyze the combat behavior and the technical structure of the finalist in all three styles. METHODS: Dartfish video analysis. RESULTS: The analysis of the finals of all three wrestling styles shows - with some differences - a tendency towards defense strategies, an application of low-risk techniques with low attractiveness and low technical versatility. The champions are starting the first effective attack normally about 3 minutes after the beginning of a bout. Only two main techniques predominate in Greco-Roman wrestling and female wrestling. CONCLUSIONS: This is a challenge for coaches in the current technical training and, in addition, for the long-term technical and tactical training concepts to develop more attractive techniques.